Glutamate. Its applications in food and contribution to health. - Selamat, Jinap; Hajeb, Parvaneh (Elsevier, 2010)
This article reviews application of glutamate in food and its benefits and role as one of the common food ingredients used. Monosodium glutamate is one of the most abundant naturally occurring amino acids which frequently added as a flavor enhancer. It produced a unique taste that cannot be provided by other basic taste (saltiness, sourness, sweetness and bitterness), referred to as a fifth taste (umami). Glutamate serves some functions in the body as well, serving as an energy source for certain tissues and as a substrate for glutathione synthesis. Glutamate has the potential to enhance food intake in older individuals and dietary free glutamate evoked a visceral sensation from the stomach, intestine and portal vein. Small quantities of glutamate used in combination with a reduced amount of table salt during food preparation allow for far less salt to be used during and after cooking. Because glutamate is one of the most intensely studied food ingredients in the food supply and has been found safe, the Joint Expert Committee on Food Additives of the United Nations Food and Agriculture Organization and World Health Organization placed it in the safest category for food additives. Despite a widespread belief that glutamate can elicit asthma, migraine headache and Chinese Restaurant Syndrome (CRS), there are no consistent clinical data to support this claim. In addition, findings from the literature indicate that there is no consistent evidence to suggest that individuals may be uniquely sensitive to glutamate.